A theoretical study of the substituent effect on reactions of amines, carbon dioxide and ethylene oxide catalyzed by binary ionic liquids. Issue 81 (6th November 2017) - Huang, Minmin; Luo, Zhoujie; Zhu, Tong; Chen, Jian; Zhang, John Zenghui; Xia, Fei
Abstract : DFT calculations indicate that the key activation barriers in the reaction of ethylene oxide and amines play an important role in determining the yields of products. Abstract : The reaction mechanisms of one-pot conversion of carbon dioxide, ethylene oxide and amines to 3-substituted-2-oxazolidinones catalyzed by the binary ionic liquids of BmimBr and BmimOAc were investigated using DFT methods. In this work, we focus on exploring how the different substituents in amines affect the yields of 3-substituted-2-oxazolidinones. The comparison of calculated free energy profiles and pathways reveals that the electronic structures of the substitutional groups in amines have a substantial influence on the nucleophilic properties of nitrogen atoms of key intermediates, which leads to a discrepancy in the activation barriers. The comparison of the calculated activation barriers of key steps and experimental yields indicates that an anticorrelation relationship exists between them. The current theoretical study inspires us to design new substrates for CO2 conversion by modulating the substituents in substrates.